Developing IELTS Material through Schoology to EFL Learners’ Listening Comprehension - Hesti Rokhaniyah; Shoffin Nahwa Utama (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
This research aims at developing IELTS listening practice tests through Schoology based on the users' needs: teachers and learners of the International Relation Department of University of Darussalam Gontor. This research applied Research and Development (R&D) design. The subjects were three IELTS listening instructors together with first semester learners encountering six meetings for IELTS listening practice tests of this on-going-semester. The findings of the research illustrated that (1) stages of IELTS listening practice tests development implemented in this research were such as need survey, materials development, validation of instruction and expert, revision, try out, revision, and final product; (2) the created product was recorded material of IELTS listening practice tests uploaded in Schoology platform, the instructors’ guide, and learners’ worksheet; (3) the product was composed of IELTS listening practice tests 1 to 6 for the first semester; (4) the criteria for IELTS listening materials are based on IELTS syllabus and the other criteria including practicality, level of difficulty, style of delivery, speed of delivery, and language content; (5) the materials of IETLS listening practice tests were appropriate for EFL learners as those materials were relevant to learners’ need and level of learners’ English ability; (6) IELTS listening practice tests could enhance learners’ excitement to learn IELTS.